2010
DOI: 10.1186/1471-2334-10-199
|View full text |Cite
|
Sign up to set email alerts
|

A prospective descriptive study of cryptococcal meningitis in HIV uninfected patients in Vietnam - high prevalence of Cryptococcus neoformans var grubii in the absence of underlying disease

Abstract: BackgroundMost cases of cryptococcal meningitis occur in patients with HIV infection: the course and outcome of disease in the apparently immunocompetent is much more poorly understood. We describe a cohort of HIV uninfected Vietnamese patients with cryptococcal meningitis in whom underlying disease is uncommon, and relate presenting features of patients and the characteristics of the infecting species to outcome.MethodsA prospective descriptive study of HIV negative patients with cryptococcal meningitis based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
126
2
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(143 citation statements)
references
References 45 publications
10
126
2
5
Order By: Relevance
“…IRIS has been described infrequently in association with C. gattii infection: occasional cases were reported in apparently healthy hosts in association with pregnancy and in immunocompromised individuals (216,217,241,299). No cases were reported for 10 HIV-negative Vietnamese patients with C. gattii meningitis (239). However, in an Australian study, IRIS occurred in 9.4% of patients, two-thirds of whom had no underlying immunocompromise, although one patient was postpartum (299).…”
Section: Immune Reconstitution Inflammatory Syndromementioning
confidence: 90%
See 3 more Smart Citations
“…IRIS has been described infrequently in association with C. gattii infection: occasional cases were reported in apparently healthy hosts in association with pregnancy and in immunocompromised individuals (216,217,241,299). No cases were reported for 10 HIV-negative Vietnamese patients with C. gattii meningitis (239). However, in an Australian study, IRIS occurred in 9.4% of patients, two-thirds of whom had no underlying immunocompromise, although one patient was postpartum (299).…”
Section: Immune Reconstitution Inflammatory Syndromementioning
confidence: 90%
“…Lower death rates of 0 to 15% were reported in three other Australian studies conducted between the late 1980s and 2007 (27,28,299). In a recent Vietnamese study, 1 of 10 C. gattii-infected patients died (239). Mortality is likely to be influenced not only by patient factors but also by medical awareness and access to health resources, which vary between countries.…”
Section: Mortality From C Gattii Cns Cryptococcosis and Prognostic Dmentioning
confidence: 93%
See 2 more Smart Citations
“…Furthermore, genotyping studies revealed that 33.9% of the isolates from Madrid, Spain, fell into the hybrid genotype cluster AFLP3 (serotype AD) and 19.6% in genotype AFLP2 (serotype D) (20). Other epidemiological surveys from Brazil, China, South Korea, Taiwan, and Vietnam revealed that serotype D isolates are rarely found or are absent (2,(9)(10)(11)29).…”
Section: Discussionmentioning
confidence: 99%